Migraine and vasospasm in glaucoma: age-related evaluation of 2027 patients with glaucoma or ocular hypertension - Gramer, Gwendolyn; Weber, Bernhard H. F.; Gramer, Eugen (Investigative ophthalmology & visual science, 2015)
PURPOSE. To evaluate frequency of migraine, vasospasm (VS), family history (FH) of migraine, and family history of glaucoma (FHG) in different types of glaucoma in relation to age and stage of visual field loss (VFL) at diagnosis. METHODS. A total of 2170 patients with glaucoma or ocular hypertension (OH) were interviewed by using standardized questions concerning FHG, age at diagnosis, and potential risk factors, including migraine and VS. Of 2027 patients providing information on migraine, 1244 had primary open-angle glaucoma (POAG), 140 normal tension glaucoma (NTG), 49 pigmentary glaucoma, 64 pseudoexfoliation glaucoma (PEX), 138 OH, and 218 primary angle closure glaucoma (PACG). RESULTS. Of all patients, 13.7% reported migraine, 19.0% VS, 30.8% FH of migraine, and 40.3% FHG. Patients with FHG had a significantly higher frequency of migraine than patients without FHG (15.7% vs. 12.3%, P ¼ 0.02). Migraine was significantly more frequent in NTG (21.4%) than POAG (13.1%; P ¼ 0.01), PEX (7.8%; P ¼ 0.02), and PACG (10.1%; P ¼ 0.004). Compared to patients with POAG, patients with NTG had a 63.5% higher age-corrected probability for migraine (P ¼ 0.007). There was no evidence for migraine or VS being prognostic factors regarding the extent of VFL at diagnosis. Migraine and VS were significantly more frequent in females. CONCLUSIONS. The higher frequency of migraine and VS in females could contribute to the female preponderance in NTG. Our findings suggest an association of NTG and migraine and a common, possibly polygenetic, vascular etiology of these two diseases both with familial predisposition.